Aquisição da morfologia flexional verbal em português brasileiro - um estudo experimental com dados de compreensão - Lima, Marcos André Ferraz de (2014)
This study has as objective to investigate the children's sensitivity to the inflectional morphemes of Brazilian Portuguese (BP) in children between 3, 4 and 5 years old, it has taken as fundamental to the acquisition of verbal morphology of this language. Studies about this topic, already realized with children were based mainly on the production of data, which demonstrated that children produce, already very early, inflectional verbal morphemes in their language. These production data follow a pattern in which it reveals the presence of irregular verb forms with regular forms in the early stages of the process. In the second moment, around 3-4 years old, decays the presence of irregular shapes, appearing irregular verbs used as regular phenomenon known as over regularization. In the final stage, there is the return to the initial default. Our study is to investigate, from the data of understanding, if the child, in the stage that produces over regularization forms, would be sensible to the presence, in the input, to irregular verb in the over regularization form. It is assumed as a hypothesis the idea that children in the age between 3 and 5 years, even thy produce phases in the over regularization forms, they are able to identify the ungrammaticality in the these verbs in the sentence produced by someone else. For this, it was mounted a grammaticality judgment the experiment in which controlled , beyond the age of the participants , the type of verb (regular, irregular and over regularization) and invented verbs, it was divided into three lists of 30 stimuli and each one with 4 conditions . For the conditions 3 and 4, the sentences are repeated in the three lists. Thus, we have for the tree lists a total of 54 stimulus.The results support the hypothesis allow assumed here, showing a sensitivity to the grammaticality of the child's verbal forms present in the input.